The amount of calcium in bony structures used for age determination in Cyprinion macrostomus (Heckel, 1843) - Aydin, Rahmi; Sen, Dursun; Calta, Metin; Canpolat, Oezguer (Wiley-Blackwell, 2008)
In this study, the ages of 76 individuals belonging to the Cyprinion macrostomus (Heckel, 1843) population caught from Murat River near Bingol city were determined from six different bony structures and the level of calcium mineral of each bony structure was measured using an atomic absorption spectrophotometer. The determined element was statistically examined according to the age, length, weight and sex of the fish. The age, length and weight ranges of the fish were found to be 2-6, 12.0-21.2 mm and 16.3-135.3 g respectively. The relationships between the accumulation of calcium in all bony structures and the fish size (both length and weight) were found to be insignificant (P > 0.05). However, a strong relationship was found between fish weight and accumulation of the mineral in vertebra and otolith. A strong correlation was also found between fish length and accumulation of calcium in the dorsal fin ray, followed by the otolith, vertebra and cleithrum bones respectively. Whereas the accumulation of calcium according to the age groups was found to be insignificant for scale and operculum (P > 0.05), it was found to be significant for all the other bony structures examined (P < 0.05). In conclusion, the accumulation of calcium on some bony structures of C. macrostomus was observed to increase with an increase in age, length and weight of fish, although the increases were not statistically significant at least for some bony structures (P > 0.05).
Keywords: Cyprinion macrostomus; calcium; age determination; Murat river